Hypokalemic Periodic Paralysis and Osteomalacia With Osteoporosis In Distal RTA as Initial Presentation of Primary Sjögren’s Syndrome: A Case Report (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Sjogren’s syndrome is a systemic autoimmune disorder of the exocrine glands with extra glandula reinvolvement in one fourth patients. Tubulointerstitial nephritis being the most common Renal pathology. The purpose of the study to reminding readers of this issue and emphasize the necessity for further research on how to deal within the best way.Case Presentation: A-30 years-aged female patient presented with recurrent hypokalemic paralysis with persistent symptoms due to coexisting osteomalacia. Distal Renal Tubular Acidosis type 1 (dRTA1) manifests as an extra glandular presentation of Sjögren Syndrome (SS). The case focused that in the setting of recurrent hypokalemia, progressive weakness should differentiate from primary hypokalemic paralysis and evaluated for dRTA1, as this conditions are potentially treatable.  Conclusion: Recurrent hypokalaemic paralysis is a rare presentation of primary Sjogren syndrome and it poses a challenge to diagnosis due to existing diagnostic criteria.JCMCTA 2024 ; 35 (2) : 182-186